2017
DOI: 10.1093/aje/kwx059
|View full text |Cite
|
Sign up to set email alerts
|

Are Lowered Socioeconomic Circumstances Causally Related to Tooth Loss? A Natural Experiment Involving the 2011 Great East Japan Earthquake

Abstract: Oral health status is correlated with socioeconomic status. However, the causal nature of the relationship is not established. Here we describe a natural experiment involving deteriorating socioeconomic circumstances following exposure to the 2011 Great East Japan Earthquake and Tsunami. We investigated the relationship between subjective economic deterioration and housing damage due to the disaster and tooth loss in a cohort of community-dwelling residents (n = 3,039), from whom we obtained information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 33 publications
2
58
0
1
Order By: Relevance
“…Similarly, the fundamental psychosocial and oral status of participants, especially residents in temporary housing at predisaster were mostly unknown. Matsuyama et al reported that the survivors’ low socio‐economic condition due to the GEJE increased the tooth loss. Since the entry criteria for relocating to prefabricated temporary housing partially included the income limits on applicants for living expenses, we cannot rule out selection bias due to low health status among low‐income people living in temporary housing.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, the fundamental psychosocial and oral status of participants, especially residents in temporary housing at predisaster were mostly unknown. Matsuyama et al reported that the survivors’ low socio‐economic condition due to the GEJE increased the tooth loss. Since the entry criteria for relocating to prefabricated temporary housing partially included the income limits on applicants for living expenses, we cannot rule out selection bias due to low health status among low‐income people living in temporary housing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, people living in prefabricated housing tended to elderly, economically disadvantaged, and health status of prefabricated housing dwellers was exacerbated over time after the GEJE, possibly due to employment and income issues at postdisaster, which were potential factors associated with toothache . Therefore, socio‐demographic characteristics, lifestyle, and health condition variables were included in the analyses as covariates such as the subjects sex, age, subjective economic status, smoking habits (“Yes” or “No”), and psychological distress using the six‐item Kessler Psychological Distress Scale (K6), and insomnia using the eight‐item Athens Insomnia Scale (AIS‐8) …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations